Evaluation of equivalent static forces for wind-resistant design of long-span roof structures from dynamic pressure data - Chandrasena, Ochini; Pennung Warnitchai; Punchet Thammarak; Thanakorn Pheeraphan; Computer and Structures Inc. (CSI), USA; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
Wind load is one of the critical loading actions on long-span roof structures. It is vital to precisely compute the wind-induced effects on these structures at the design stage. It is challenging to determine the wind-induced dynamic responses of long-span roof structures due to their complex body-induced turbulence and dynamic properties. The prevailing design practices usually require converting the dynamic-wind effects into the Equivalent Static Wind Forces (ESWF). The ESWF produces the static load distributions whose static results are like the maximum dynamic response under the actual wind loading behaviour. Thus, the wind-induced excitation is indicated concerning a static force through ESWF. This load illustration permits structural designers to pursue a reasonably straightforward static analysis approach in evaluating the building performance to wind loads, avoiding the complex random dynamic analysis. This research aims to evaluate the equivalent static wind force patterns for a long-span dome structure by applying the theory for computing the equivalent static wind force, which comprises mean, background, and resonant components, using dynamic pressure data. The second objective is to verify the results of the equivalent static wind force responses by cross-checking the equivalent static wind force patterns of the dome structure with the corresponding dynamic-wind responses for each component. The results reveal that this ESWF approach can be applied to this considered long-span dome structure. Each of the ESWF components can be verified by the dynamic responses obtained by time-history analysis. It could accurately predict the corresponding mean, background, and resonant response. Moreover, the combined equivalent static wind load effects could precisely estimate the maximum dynamic wind load effects. Although the theory of ESWF can evaluate the composition of this complicated wind response for complex structures like long-span dome structures, the most practical solution is to conduct a time-history analysis to study the wind-induced responses of the system, compared to the ESWF approach.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2021
Keywords: Wind resistant design; Roofs, Suspension